As implicações filosóficas da teoria da Gestalt - Cholfe, Jonas Fornitano (Universidade Federal de São Carlos, 2009)
The Gestalt Theory, which foundations are erected by the ideas of Köhler, Koffka and Wertheimer, has as main purpose the reestablishment of the bond between science and life. The notion of Gestalt, thought as an entity that has meaning and value as intrinsic characteristics, is the key of this enterprise. Starting from the phenomenological thesis , the defense that the conceptual understanding demands going back to the data of the direct experience, the gestaltists find in their basic category the possibility of a conception of nature that surpasses the consequences of the materialism, that is, the reduction of the most important features of the human mind to mere subjective illusion. The presence of significant configurations in the early perceptive processes, in thought and in the theoretical entities of physical science, will support the proposal of a Science that, when exceeding the life world, will not discard its more important characteristics, that is, its intelligible relations, based in the intrinsic characteristics of the parts of a totality. At the same time, however, the gestaltists defend a dualism between the phenomenal world, known directly, and the transphenomenal world, which is known only indirectly - it's constructed in the interaction between the scientific theory and the facts collected by the experiments. This dualism results in the "naturalism" in the Gestalt Theory, of which the isomorphism hypothesis is the better expression. Such naturalism is the main target of the critics from the philosophical phenomenology (Husserl and Merleau-Ponty). We are to show that the defense of the physical world as an reality appart from the consciousness corresponds to an assumption supported by the direct experience, as is demanded by the phenomenological thesis. In the transphenomenal transcendence experience", we find the transphenomenal term as condition of meaning of the phenomenal term, therefore, the phenomenological argument that would give meaning to transphenomenality . We can point as contributions of our research the understanding of the epistemological dualism of Gestalt Theory, as well as the survey of questions directed to the phenomenological philosophy.
Keywords: Percepção; Gestaltismo; Fenomenologia; Transcendência (Filosofia); Gestalt; Natureza; Isomorfismo; Phenomenology; Gestalt; Phenomenal world; Nature; Isomorphism; CIENCIAS HUMANAS::FILOSOFIA